Use of Real-Time PCR To Resolve Slide Agglutination Discrepancies in Serogroup Identification of Neisseria meningitidis - Mothershed, Elizabeth A. (American Society for Microbiology, 2004)
Neisseria meningitidis is a leading cause of bacterial meningitis and septicemia in children and young adults in the United States. Rapid and reliable identification of N. meningitidis serogroups is crucial for judicious and expedient response to cases of meningococcal disease, including decisions about vaccination campaigns. From 1997 to 2002, 1,298 N. meningitidis isolates, collected in the United States through the Active Bacterial Core surveillance (ABCs), were tested by slide agglutination serogrouping (SASG) at both the ABCs sites and the Centers for Disease Control and Prevention (CDC). For over 95% of isolates, SASG results were concordant, while discrepant results were reported for 58 isolates. To resolve these discrepancies, we repeated the SASG in a blinded fashion and employed ctrA and six serogroup-specific PCR assays (SGS-PCR) to determine the genetic capsule type. Seventy-eight percent of discrepancies were resolved, since results of the SGS-PCR and SASG blinded study agreed with each other and confirmed the SASG result at either state health laboratories or CDC. This study demonstrated the ability of SGS-PCR to efficiently resolve SASG discrepancies and identified the main cause of the discrepancies as overreporting of these isolates as nongroupable. It also reemphasized the importance of adherence to quality assurance procedures when performing SASG and prompted prospective monitoring for SASG discrepancies involving isolates collected through ABCs in the United States.